Pediatric diabetes in China: Challenges and actions. Issue 5 (24th April 2022) - Wang, Jinling; Wu, Wei; Dong, Guanping; Huang, Ke; Fu, Junfen
Abstract: Pediatric diabetes is growing in China. The annual incidence of childhood type 1 diabetes is about 2.02–5.3 per 100, 000 person‐years. Type 2 diabetes in children and adolescents is increasing dramatically with the high‐speed urbanization of China. The prevalence of type 2 diabetes varies from 1.64/100, 000 to 15.16/100, 000 based on the geography and economy. Monogenic diabetes used to be underestimated in China and now more cases are emerging. In this review, we give an overview of pediatric diabetes in China, present the progresses and challenges in management of pediatric diabetes, and discuss the government policy and potential actions in China, for better life quality of diabetic families.